Some Observations in Forests of Austria - Shukla, R. S. (Indian Forester, 1983)
Based on the first hand information collected by the author this paper presents short account of the various administrative and technical details of the temperate forests of Austria. An account of podsolic soil, phenomenon of temperature inversion and consequently inversion of vegetation succession, silviculture, logging, marketing, wild life and forest management aspects contained herein, are quite revealing and interesting. The silvicultural practiees aiming at the concept of natural automaton, the high rate of mean annual increment, productivity and financial consideralions, regarding the Norway Spruce, White fir and Beech have also been dealt with.